2021
DOI: 10.1186/s40644-020-00371-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of naive indolent lymphoma using whole-body diffusion-weighted imaging and T2-weighted MRI: results of a prospective study in 30 patients

Abstract: Background We prospectively evaluated the diagnostic utility of whole-body diffusion-weighted imaging with background body signal suppression and T2-weighted short-tau inversion recovery MRI (WB-DWIBS/STIR) for the pretherapeutic staging of indolent lymphoma in 30 patients. Methods This prospective study included 30 treatment-naive patients with indolent lymphomas who underwent WB-DWIBS/STIR and conventional imaging workup plus biopsy. The prethera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Funnel plot and Egger's test did not indicate asymmetry of the distribution of results among studies (P=0.75, Figure S9). Most studies (n=11) reported agreement in the principal stages, one study (22) included E and S modifiers, where present. A single study (21) that reported agreement based on the Lugano criteria, was not included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Funnel plot and Egger's test did not indicate asymmetry of the distribution of results among studies (P=0.75, Figure S9). Most studies (n=11) reported agreement in the principal stages, one study (22) included E and S modifiers, where present. A single study (21) that reported agreement based on the Lugano criteria, was not included.…”
Section: Resultsmentioning
confidence: 99%
“…All wbMRI studies acquired at least two b values. The acquisition was performed in the transverse plane except for one study (22), which acquired head and neck in the transverse plane and the rest of the body in the coronal plane. Two studies (7,11) used respiratory triggering for DWI.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Whole Body Diffusion MRI (WB-DW MRI) has been proposed as a possible alternative to PET/CT [25,26]. It has also been demonstrated that WB-DW MRI is less histology dependent than PET/CT and thus is likely to become the imaging test of choice for staging indolent lymphomas with low FDG avidity in a short time frame [27][28][29].…”
Section: Discussionmentioning
confidence: 99%